Tinjauan Kriminologis Terhadap Preman yang Melakukan Kejahatan (Studi Kasus Polsek Batangtoru) - Marwan Busyro (Universitas Medan Area, 2019)
This paper will write about crimes committed by thugs in criminological studies. The purpose of this study are the factors that cause thugs to commit crimes in Batangtoru and head sector police made by the Batangtoru police sector against thugs in Batangtoru. The research method is normative which studies the study of documents using secondary data such as statutory regulations. Based on the results of this study found factors causing thugs to commit crimes in Batangtoru regarding environmental factors, economic factors, educational factors, alcoholic drinks (alcohol). In addition, regarding crimes of thugs in Batangtoru such as the availability of free time that cannot be used for other activities, consumptive lifestyles that are accompanied by reduced work interest or job opportunities. Whereas the efforts to overcome thuggery in Batangtoru, namely the Batangtoru Sector Police, have taken preventive and repressive measures. In addition to preventive measures, the Batangtoru Police Station also took repressive efforts to crack down on thuggery actions that occurred in the community. Repressive efforts are carried out by carrying out street crime operations by raiding and cracking down on thugs in the community.